Host Defense against Mycobacterium avium Does Not Have an Absolute Requirement for Major Histocompatibility Complex Class I-Restricted T Cells - Bermudez, Luiz E. (American Society for Microbiology, 1999)
The role of CD8(+) T cells was evaluated in a mouse model of disseminated Mycobacterium avium infection. C57BL/6J and C57BL/6Jβ(2)(−/−) (β(2)(−/−)) mice were infected intravenously, and the number of viable bacteria in each liver and spleen was determined. No significant difference between the number of bacteria in the two strains of mice was observed at 2, 4, 6, and 8 weeks after infection. Histopathological examination of granulomas from C57BL/6J and β(2)(−/−) mice did not show any difference either in the number of organisms per granuloma or in the size of the granulomas. Investigation of the cytokine profile in the spleen demonstrated that the β(2)(−/−) strain of mice produced a significantly lower amount of gamma interferon at 8 weeks after infection and significantly increased concentrations of tumor necrosis factor alpha compared with that from the wild-type mouse. Interleukin-12 and transforming growth factor β(1) levels did not differ between the two strains of mice at 2, 4, 6, and 8 weeks. Although previous work had found that host response against Mycobacterium tuberculosis involves major histocompatibility complex class I-restricted T cells, our results indicate that chronic deficiency of CD8(+) T cells does not lead to a different expression of the disease and that if CD8(+) T cells are involved in the host response, their function can be assumed by other immune cells.